2016
DOI: 10.1111/cdev.12497
|View full text |Cite
|
Sign up to set email alerts
|

Development of Teleological Explanations in Peruvian Quechua‐Speaking and U.S. English‐Speaking Preschoolers and Adults

Abstract: However, changes with age were importantly distinct from differences corresponding to cultural variation. Developmental and cultural differences in teleological explanations may reflect causal analysis of the features under consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…To our knowledge, teleological reasoning has been studied in only one non-Western culture previously (indigenous Quechua-speakers in Peru), but in this culture, participants were expected to show a strong teleological bias due to high levels of explicit teleological and agentic talk about natural phenomena (Sanchez Tapia et al, 2016; Gelman et al, 2015). By contrast, the present research focused on a stronger test of universality: whether broad teleological tendencies develop in a culture that is not only non-WEIRD, but is one of the least explicitly theistic in the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, teleological reasoning has been studied in only one non-Western culture previously (indigenous Quechua-speakers in Peru), but in this culture, participants were expected to show a strong teleological bias due to high levels of explicit teleological and agentic talk about natural phenomena (Sanchez Tapia et al, 2016; Gelman et al, 2015). By contrast, the present research focused on a stronger test of universality: whether broad teleological tendencies develop in a culture that is not only non-WEIRD, but is one of the least explicitly theistic in the world.…”
Section: Discussionmentioning
confidence: 99%
“…The development of teleological reasoning has been studied in a single non-Western culture (indigenous Quechua-speakers in Peru). In this culture, participants showed a greater bias to endorse teleological explanations when scientifically unwarranted; however, Quechua culture contains high levels of explicit teleological and agentic talk regarding natural phenomena, which could account for this bias (Sanchez Tapia et al, 2016; Gelman, Mannheim, Escalante & Sanchez Tapia, 2015). Thus, data from Quechua speakers cannot answer the question of universality: A key test is whether the teleological bias remains present even in more secular non-WEIRD populations.…”
Section: Introductionmentioning
confidence: 87%
“…Students who use teleological thinking tend to explain natural selection inaccurately in terms of organisms' needs rather than as the change in the frequency of traits within a population due to the comparative advantage that certain traits have over others in a given environment. Other studies, however, have shown that children and adults in Indigenous communities with low educational attainment may not exhibit more teleological reasoning than Western educated individuals (Sánchez Tapia et al, ); yet other authors have proposed that teleological reasoning may indeed indicate knowledge on ecological interactions (ojalehto, Waxman, & Medin, ). Since the extent of teleological reasoning among non‐Western communities is still contended in the published literature, and the Nahua people have been described as harboring deep knowledge of ecological interactions (Rodríguez & Hasler, ), we assessed whether adults and seventh grade students in this community exhibited teleological reasoning and, if so, to what extent.…”
Section: Study 1 Reasoning Patterns Of Nahua Students: Teleologymentioning
confidence: 97%
“…Only a few studies in the field of developmental psychology (Evans & Rosengren, ; Kelemen, ; Kelemen, Emmons, Schillaci, & Ganea, ) explore the learning of natural selection with the tools of developmental psychology, but those do not include a social justice perspective oriented to empowering learners from ethnic minority groups. Our approach is innovative, in that we integrate these approaches, building on the traditions of Culturally Relevant Pedagogy (Kawagley et al, ; Ladson‐Billings, ) and Border‐crossing (Aikenhead, , ), while adding the dimension of cultural cognition (Sánchez Tapia et al, ; Waxman, Medin, & Ross, 2007). Our integrated perspective accounts for the different factors that influence students' prior knowledge, responding to the learners' worldviews in their cognitive, social, cultural, and historical contexts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation